Genome assemblies of Nuttall’s White-crowned sparrow (Zonotrichia leucophrys nuttalli) and Rufous-collared sparrow (Zonotrichia capensis) - Zhou Wu; Katarzyna Miedzinska; Jesse S. Krause; Paulina L. Gonzalez-Gomez; Jonathan H. Pérez; John C. Wingfield; Simone L. Meddle; Jacqueline Smith (Scientific Data)
Abstract The Zonotrichia sparrows, belonging to the Passerellidae family, are widely studied for their vocalizations and genetic diversity. Here, we present two high-quality genome assemblies for Zonotrichia species; the northern hemisphere Nuttall’s white-crowned sparrow (Zonotrichia leucophrys nuttalli, NWCS) and the southern hemisphere rufous-collared sparrow (Zonotrichia capensis chilensis, RUFS). These assemblies were assembled using PacBio long-reads and Omni-C chromatin conformation technology, integrated with RNA-sequencing data to provide genome annotations. The NWCS assembly comprises 1.12 Gb anchored to 30 chromosomes, while the RUFS assembly includes 1.11 Gb on 27 chromosomes. Both assemblies exhibit high completeness and contiguity, with 96.6% and 96.9% complete BUSCOs (Benchmarking Universal Single-Copy Orthologs) for NWCS and RUFS, respectively. These genome assemblies provide valuable resources for future research on genetic divergence, vocal learning, evolution and responses to climate change within the Zonotrichia genus.